Święte 20: Graves of the Corded Ware Culture - Dobrakowska, Teresa; Włodarczak, Piotr (Baltic-Pontic Studies, 2018)
Archaeological excavations at site 20, Święte, Radymno Commune, Jarosław District, were prompted by construction of the A4 motorway. Among the results the site has yielded there are two Corded Ware graves. Both of them are niche constructions datable to the younger Corded Ware phase in Małopolska. Accommodating three interments, grave 43 is particularly interesting for the re-use of its burial chamber and re-deposition of disarticulated older human remains. Grave goods within the graves are typical of the younger Corded Ware phase, with parallels found at closely located sites of the Lower San Valley and Rzeszów Foothills. The absolute date range for both graves has been determined to be ca. 2550-2400 BC.